MEASURES TO IMPROVE THE OPERATION OF PASSENGER TRANSPORT AND URBAN MOBILITY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the types of urban electric transport used in Belarusian cities, gives a detailed classification and comparison of available vehicles. Various options for increasing the share of environmentally friendly transport through the use of electric buses and trolleybuses are considered, an assessment and a comparative analysis of the options are given. Features of planning of work of drivers and drawing up of the schedule taking into account safety requirements are considered. Intensive growth in the level of motorization of the population, an increase in the number of business trips, the use of light vehicles with small volumes of freight, the emergence of "commercial" routes have led in recent years to a sharp increase in car flows in urban transport systems. In this regard, a whole range of tasks arises related to increasing the comfort of movement and the quality of life of citizens in general, which is possible by optimizing the operation of route (urban) passenger transport and increasing its attractiveness for users of all levels. Experimental and computational-theoretical studies were carried out, the direction to improve the work of route passenger (urban) transport of cities (on the example of Polotsk and Novopolotsk). Recommendations are given for further improving the operation of urban passenger transport systems according to alternative scenarios for the cities of Polotsk and Novopolotsk. An assessment is made of the possibility of achieving planned indicators for reducing greenhouse gas emissions from the implementation of the pilot project measures aimed at improving the quality and efficiency of the route passenger transport in these cities. A comparative analysis of the possibility of developing various types of electric route passenger transport is carried out. A map has been developed for reducing emissions of pollutants from vehicles with a change in the structure of mobility of the population and an increase in the share of use of route passenger transport, an increase in the speed of movement of route passenger transport.